Intravenous immunoglobulin for cystic fibrosis lung disease: a case series of 16 children. Issue 4 (19th March 2004) - Balfour-Lynn, I M; Mohan, U; Bush, A; Rosenthal, M
Abstract : Background and objective: Some children with severe cystic fibrosis (CF) lung disease develop chest tightness, recurrent dry cough, and intractable wheeze, often accompanied by deteriorating lung function and failure to expectorate sputum. In an attempt to reduce the use of regular oral corticosteroids, we treated a group of such children with monthly courses of intravenous immunoglobulin (IVIG). Methods: This is a retrospective case note review of 16 children, aged 3–16 years (median 13.0 years) who received 1–66 (median 7.5) courses of monthly IVIG, at a dose of 1 g/kg on two successive days for the first dose, followed by 1 g/kg monthly as a 12 hour infusion, with corticosteroid and antihistamine cover. Results: FEV1 improved from a median (95% confidence interval (CI)) of 50% (39 to 61%) to 54% (48 to 66%), with a median (95% CI) difference of +7.5% (−1.5 to 14.5%; NS). FVC improved from 65% (60 to 77%) to 83% (70 to 89%), with a difference of +13% (4 to 22%, p = 0.01). The total daily dose/kg body weight of oral prednisolone was reduced from 0.6 (0.3 to 1.0) to 0 (0 to 0.1) mg/kg/day, with a reduction of −0.6 (−1.0 to −0.1, p = 0.006) mg/kg/day. The total daily dose of inhaled corticosteroid (budesonide equivalent) was a median (range) of 2000 μg (800–6000 μg), which was reduced to 1500 μg (0–3200 μg). The median (95% CI) difference was −400 μg (−1600 to 0 μg), p<0.05. IVIG was well tolerated and the regimen acceptable to all but one of the children. The following transient adverse reactions were seen in only one patient each: headache, fever, hypotension, aseptic meningitis, and chest tightness. Conclusion: We suggest that an n = 1 trial of IVIG in carefully selected patients with severe obstructive CF lung disease is worth considering, as for some it may lead to significant benefit.